Perancangan dan Implementasi Sistem Monitoring Kecepatan dan Proteksi Motor Induksi 3 Phase Berbasis LabView - TRILESTARI, SITI; Andriana; Irvan Budiawan (Department of Electrical Engineering, UNJANI, 2023)
Three-phase induction motors are one of the main components in various industries. To ensure optimal performance and prevent damage to the motor, a reliable speed monitoring and protection system is needed. Considering the difficulty of technicians or engineers in monitoring induction motors in a factory, this is the main thing that is happening at the moment. In this research, researchers designed and implemented a LabVIEW-based 3-phase induction motor speed monitoring and protection system using a Variable Speed ​​Drive (VSD) and controlled by OUSEAL PLC. The monitoring system design or as an HMI (Human Machine Interface) was designed using LabVIEW software via RS-485 serial communication using the Modbus RTU (Remote Terminal Unit) protocol. To set the desired motor rotation speed, namely by changing the frequency value entering the motor, this setting can be adjusted via the LabVIEW interface. Furthermore, the protection system is designed using the error code feature found on the VSD and uses a thermocouple sensor to protect the motor temperature so that if the system experiences a disturbance, the induction motor will stop automatically and then display the error code or disturbance that occurred. The designed system works in accordance with the design, control and monitoring of the rotation speed of a 3 phase induction motor which can be controlled using the LabView application interface. From the results of the research that has been carried out, it is stated that changes in the frequency value entering a 3-phase induction motor will result in a faster rotation speed of the motor produced.